Application of in situ stress estimation methods in wellbore stability analysis under isotropic and anisotropic conditions - Gholami, Raoof; Rasouli, V.; Aadnoy, B.; Mohammadi, R. (2015)
© 2015 Sinopec Geophysical Research Institute. Estimation of in situ stresses is a key step in many petroleum engineering applications, ranging from wellbore stability to sanding analysis and hydraulic fracturing design. Direct techniques conventionally used to determine in situ stresses are indeed very time consuming and expensive. These measurements would also be restricted as to the depth of acquisition, and generalization of the results to entire rock masses may not yield representative results. In this paper, applications of three indirect methods-Zoback's polygon, shear moduli, and poroelastic-are studied to assess their applicability in providing reliable stress estimation under isotropic and anisotropic conditions. Determination of elastic, strength, and in situ stress parameters according to the assumption of each method for one of the vertical wells drilled in south Iran indicated that the shear moduli method is an appropriate approach for prediction of maximum horizontal stress within an interval where sufficient field data including leak-off tests are acquired. However, the poroelastic method seems to be a better method in prediction of in situ stresses under anisotropic conditions. This might be due to the presence of excessive shale formations in subsurface layers, causing structural or intrinsic anisotropy-based methods such as poroelastic equations to deliver more accurate results. However, making general conclusions based on studying a single vertical wellbore may not be sufficient, and therefore further studies are required.